스피어피싱 방지를 위한 DID 기반 이메일 시스템 - 오한수 (The Graduate School, Ajou University, 2024)
개인정보와 자기주권 신원인증이 대두 되면서 다양한 산업에서 블록체인과 DID가 사용되고 있다. 특히나 개인에 대한 정보나 사원증을 물리적인 모형이나 단순 디지털 아이디를 넘어서 블록체인 기술인 DID를 적용하여 탈바꿈 하고 있다. 특히나 블록체인과 DID기술이 탈중앙화와 신뢰성문제, 무결성문제를 해결하면서 수많은 네트워크의 체계도 바꾸어가는 연구가 많이 진행 중이다._x000D_ 그 중 전통적인 이메일 시스템에서도 수많은 연구가 진행중이다. 현재 이메일 시스템이 연구되어 사용된 것은 20년도 넘었으며, 해당 시스템을 조금씩 보완하여 사용중이다. 하지만 악성사용자들의 수준도 높아지고, 기술도 정교해지면서 2023년에 이르러서도 피싱과 스피어피싱에 대한 손해가 이어지고 있다. 하지만 사용자들은 복잡한 보안 프로토콜이나 인증서 관리의 어려움으로 이메일 보안을 잘 유지하지 못하고 있는 실정이다. 또한 디지털 인증서나 전자서명을 사용함에 있어서도 중앙집중 형태인 CA의 부정 발급사건도 많고, 공격자들이 교묘하게 인증서를 도용하는 등 피해는 여전히 진행 중이다._x000D_ 본 논문은 DID 사용자 인증에 있어서, 실제 세계에서의 신원 확인과 접근 관리를 넘어서 스피어피싱 방지라는 디지털 커뮤니케이션의 안전성 강화에 중점을 둔 연구이다. 본 논문에서 제안한 DID 기반 시스템은 기존의 S/MIME와 PGP 방식과 비교하여 중앙 집중식 인증 기관에 의존하지 않고, 사용자의 신원 정보를 더 안전하고 효율적으로 관리하며, 키 관리나 키 교환의 신뢰성을 증가시킨다. 또한, 이메일의 무결성과 발신자의 신원을 검증하여 스피어피싱 공격을 방지하는데, 이를 시스템을 제안하며 보안석 분석과 이론적 분석을 통해 설명하였다.|As personal information and self-sovereign identity authentication emerge, blockchain and DID are being used in various industries. In particular, personal information and employee ID cards are being transformed beyond physical models or simple digital ID by applying blockchain technology, DID. In particular, much research is underway to change the systems of numerous networks as blockchain and DID technologies solve decentralization, reliability, and integrity issues._x000D_ Among them, a lot of research is underway on traditional email systems. The current email system has been researched and used for over 20 years, and the system is being gradually improved. However, as the level of malicious users increases and technology becomes more sophisticated, losses from phishing and spear phishing are continuing even into 2023. However, users are having difficulty maintaining email security due to complex security protocols or difficulties in certificate management. In addition, when using digital certificates or electronic signatures, there are many cases of fraudulent issuance by centralized CAs, and damage is still ongoing, with attackers cleverly stealing certificates._x000D_ In DID user authentication, this study focuses on strengthening the safety of digital communication, including preventing spear phishing, beyond identity verification and access management in the real world. Compared to the existing S/MIME and PGP methods, the DID-based system proposed in this paper does not rely on a centralized certification authority, manages user identity information more safely and efficiently, and increases the reliability of key management and key exchange. I order it. In addition, the integrity of the email and the identity of the sender are verified to prevent spear phishing attacks. This system was proposed and explained through security analysis and theoretical analysis.
학위논문(석사)--사이버보안학과,2024. 2
Keywords: Blockchain; DID; Email system; Spear-phishing